Pelaksanaan Kegiatan Kunjungan Rumah (Home Visit) di SMP Negeri Tumu Kabupaten Timor Tengah Selatan - Nubatonis, Nonci; Lohmay, Imanuel; Indrawan, Putu Agus; Apriliana, I Putu Agus (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
The purpose of this study was to find out the implementation of counseling teacher home visits in dealing with student delinquency and the factors that influence the implementation of home visits for counseling teachers in overcoming student delinquency at Tumu State Junior High School, Amanuban Tengah District. South Central Timor. This type of research is phenomenalogy with a qualitative approach. The subject of this research is guidance counseling teachers while the object of this research is the implementation of home visits in overcoming student delinquency. The informants in this study were guidance counseling teachers, totaling 2 people. Data collection techniques used interviews, observation and documentation. The data analysis technique used was narrative. The results showed that: the implementation of home visits for Counseling Teachers in overcoming student delinquency at Tumu State Junior High School, Central Amanuban District, South Central Timor Regency was carried out by 2 counseling guidance teachers. each counseling guidance teacher prepares everything needed to carry out home visits starting from planning, implementing, evaluating, and following up. Home visiting activities carried out must also be carried out in collaboration with other school parties such as: Principals, homeroom teachers, subject teachers, and so on.